The Effect of the Implementation of Accounting Information Systems and Internal Audit on The Quality of Financial Statements with Organizational Commitment as a Moderating Variable (Empirical Studies at PT. Eastern Pro Engineering) - Kasdan, Kasdan (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2023)
This research aims to determine the effect of implementing accounting information systems (X1) and internal audit (X2) on the quality of financial reports (Y) with organizational commitment (Z) as a moderating variable at PT. Eastern Pro Engineering. This type of research is quantitative with the method used being descriptive associative and the data analysis design is Moderated Regression Analysis (MRA), using questionnaire data filled in by 36 respondents. The results of this research are that organizational commitment as a moderating variable does not moderate the influence of the application of accounting information systems and internal audit on the quality of financial reports with a significant t test value of >5% or 0.890 (X1) and 0.551 (X2) in equation 3, so H0 is accepted and Ha rejected.